Predictive Model of Passengers Trans Metro Bandung Encouraging Smart Transportation - Nova Nurviana; Sigit Kusumo Ati; Hani Purwati Hanifah (Jurnal Sistem Cerdas, 2019)
Smart city can be accomplished by merging all components to be smart system. One of significant components is transportation. Everybody moves, everybody need to reach other place safely, efficiency, and comfortably. In order to get smart, we have to analyze the best way to improve capability. One of the best ways is to make predictive model that one may conceive strategies attracting passengers. Using Bayesian dan SVM as comparison will produce best fit model for Trans Metro Bandung passenger data. Better strategy is an emergence needed to produce Trans Metro Bandung better performance because the model predicted there will be no significant growth for Trans Metro Bandung passenger